Penyuluhan Kesehatan Tentang Cegah Anemia pada Ibu Hamil di Puskesmas Padang Tiji Kabupaten Pidie - Faradilla Safitri; Asmaul Husna; Rauzatun Sakdiah (JURNAL PENGABDIAN KEPADA MASYARAKAT BIDANG KESEHATAN, 2021)
Anemia is a blood disorder that commonly occurs when the level of red blood cells (erythrocytes) in the body becomes too low. Pregnant women are said to have anemia if the concentration of hemoglobin (Hb) levels is <11.0 gr / dl. The contribution of anemia in pregnancy to maternal mortality in Indonesia is estimated at 10% to 12%. During pregnancy, the amount of iron needed is much greater than that of non-pregnant women. There are many bad effects that can be caused when pregnant women experience anemia. Community Service Activities are a form of the contribution of Ubudiyah University Faculty of Health Sciences lecturers in the implementation of higher education tridharma. This activity is also expected to improve the health status of mothers and children. The service that has been carried out in this activity is in the form of health education with the theme "Prevent anemia in pregnant women". This health counseling was carried out at the Padang Tiji Community Health Center, Pidie Regency, which was held on Monday, January 11, 2021 starting at 10:00 a.m. until finished, the total number of pregnant women who attended the health counseling was 18 people. The implementation of this health education is in collaboration with the Padang Tiji Community Health Center, Pidie DistrictÂ Keywords: pregnancy anemia